2021
DOI: 10.1186/s12967-021-02952-w
|View full text |Cite
|
Sign up to set email alerts
|

Molecular subtype identification and prognosis stratification by a metabolism-related gene expression signature in colorectal cancer

Abstract: Background Metabolic reprograming have been associated with cancer occurrence and progression within the tumor immune microenvironment. However, the prognostic potential of metabolism-related genes in colorectal cancer (CRC) has not been comprehensively studied. Here, we investigated metabolic transcript-related CRC subtypes and relevant immune landscapes, and developed a metabolic risk score (MRS) for survival prediction. Methods Metabolism-relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 49 publications
0
40
0
Order By: Relevance
“…In addition, recent studies have focused on the relationship between metabolism and survival: pan-cancer studies have indicated that tumor subtypes with different MAG expression patterns lead to significantly different survival [ 10 , 11 ]. Moreover, several risk models based on MAGs have been proposed for breast cancer [ 6 ], colorectal cancer [ 12 ], gastric cancer [ 13 ] and osteosarcoma [ 14 ]. However, the value of MAGs in DLBCL subtype identification and prognostic prediction remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, recent studies have focused on the relationship between metabolism and survival: pan-cancer studies have indicated that tumor subtypes with different MAG expression patterns lead to significantly different survival [ 10 , 11 ]. Moreover, several risk models based on MAGs have been proposed for breast cancer [ 6 ], colorectal cancer [ 12 ], gastric cancer [ 13 ] and osteosarcoma [ 14 ]. However, the value of MAGs in DLBCL subtype identification and prognostic prediction remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies showed prognostic models contributed to clinical decision and precision medicine ( Zhang et al, 2020 ; Mohammed et al, 2021 ). The patients were divided into high- and low-risk groups for prediction of overall survival according to the risk stratification in the prognostic models ( Lin et al, 2021 ). It is critical for improvement of the personalized therapies and the quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Lipid metabolism plays an important role in maintaining of cellular homeostasis ( Rohrig and Schulze, 2016 ; Bian et al, 2021 ). Numerous studies have demonstrated that lipid metabolism was involved in the progression, recurrence and tumor microenvironment (TME) of CRC ( Lin et al, 2021 ). Dysregulation of lipid metabolism occurs in multiple cancers, including CRC ( Dias et al, 2019 ; Haffa et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…In short, RDPS represents high predictive accuracy for predicting prognosis in CRC patients. In order to compare our RDPS model with published metabolism-related signatures, we applied the compareC R package to compare the performance among these signatures (28)(29)(30)(31)(32). As illustrated in Figure S1, our RDPS model ranked first in the predictive power in TCGA-CRC, GSE17536, and GSE29621.…”
Section: Rdps Was Well Validated In Four Cohorts and Could Be Used As A Crc Recurrence Risk Assessment Factormentioning
confidence: 99%